Implementasi Teknologi Internet of Things (IoT) pada Pengawasan Kualitas Air Sungai Mahakam Secara Real-Time - Putri Nur Halizah; Dwi Titi Maesaroh; Ansar Rizal (Lembaga Pengembangan Kinerja Dosen, 2026)
River water quality acts as a key benchmark for preserving ecological harmony and community well-being, particularly for the Mahakam River, which plays a vital role in everyday activities across East Kalimantan. That said, traditional manual monitoring falls short on time savings and steady data flow. This research focuses on deploying Internet of Things (IoT) tech for a real-time water quality tracking system on the Mahakam River. The approach involves designing and setting up a system with a NodeMCU ESP8266 microcontroller linked to a pH sensor for acidity levels, a Total Dissolved Solids (TDS) sensor for dissolved particles, and a DS18B20 temperature sensor. Measurement data gets sent over the internet, letting users check water status right away on a monitoring device or OLED screen. Testing shows the system runs reliably, delivering ongoing water quality metrics. Recorded pH levels sat between 6.5 and 7.2, with TDS from 120 to 350 ppm—meaning the water stays within safe norms, though affected by nearby environmental actions. This setup simplifies automatic, ongoing water quality oversight and boosts smart tech-driven resource management.